2019
DOI: 10.1136/bmjspcare-2019-001862
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effects of long-acting granulocyte colony-stimulating factor for febrile neutropenia in newly diagnosed patients with epithelial ovarian cancer: a randomised controlled study

Abstract: ObjectiveThis study explored the prophylactic effects of long-acting granulocyte colony-stimulating factor (G-CSF) for febrile neutropenia (FN) in newly diagnosed patients with epithelial ovarian cancer (EOC).MethodsPatients were randomised into a study group (long-acting G-CSF for all chemotherapy cycles) and a control group (short-acting G-CSF for first cycle and treatment per physician discretion for subsequent cycles) at a ratio of 1:2. The incidences of FN and myelosuppression and the number of clinical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For example, ticlopidine, captopril, and cinepazide maleate, which are used to treat cardiovascular and cerebrovascular diseases, can cause neutropenia [46][47][48][49][50]. In the previous studies, there was a correlation between the use of G-CSF and the occurrence of neutropenia or FN [33,[51][52][53]. However, we did not come to the same conclusion.…”
Section: Discussionmentioning
confidence: 61%
“…For example, ticlopidine, captopril, and cinepazide maleate, which are used to treat cardiovascular and cerebrovascular diseases, can cause neutropenia [46][47][48][49][50]. In the previous studies, there was a correlation between the use of G-CSF and the occurrence of neutropenia or FN [33,[51][52][53]. However, we did not come to the same conclusion.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have found that using a gradual dosing scale, where incremental increase in Pegfilgrastim dose over the span of a few treatment cycles can reduce risks of AEs. [4] These studies claim that since Pegfilgrastim is intrinsically a long-acting G-CSF, prophylactic scaled dosing can gradually increase neutrophil counts to protect against FN, but simultaneously maintain an optimal clearance rate. As such, these patients can avoid some Pegfilgrastim induced AEs, including LCT and HLCT.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Clinically, Pegfilgrastim is used as a primary prophylactic agent to reduce the incidence of chemotherapy-induced febrile neutropenia (FN), a poten-tially life-threatening condition. [3,4] Additionally, Neulasta has its own side effects such as pain in the extremities, bone pain, and fatigue. [3] The recommended dose of 6 mg in adults is typically given 24 hours post chemotherapy to avoid adverse effects, but simultaneously protect patients from FN.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, serum concentration of rhG-CSF becomes more stable, and the elimination half-life gets prolonged [4] . Previous clinical studies showed that PEG-rhG-CSF had good efficacy and safety, and exhibited a more convenient treatment regimen than rhG-CSF [5][6][7] . In recent studies, further comparison was performed and showed that PEG-rhG-CSF is as effective and safe as rhG-CSF for prophylaxis of chemotherapy-induced neutropenia [8,9] .…”
Section: Introductionmentioning
confidence: 99%